Design of C3N4‐Based Hybrid Heterojunctions for Enhanced Photocatalytic Hydrogen Production Activity. Issue 5 (3rd February 2020) - Yan, Fengpo; Wu, Yonghua; Jiang, Linqin; Xue, Xiaogang; Lv, Jiangquan; Lin, Lingyan; Yu, Yunlong; Zhang, Jiye; Yang, Fugui; Qiu, Yu
Abstract: Semiconductors and metals can form an Ohmic contact with an electric field pointing to the metal, or a Schottky contact with an electric field pointing to the semiconductor. If these two types of heterojunctions are constructed on a single nanoparticle, the two electric fields may cause a synergistic effect and increase the separation rate of the photogenerated electrons and holes. Metal Ni and Ag nanoparticles were successively loaded on the graphitic carbon nitride (g‐C3 N4 ) surface by precipitation and photoreduction in the hope of forming hybrid heterojunctions on single nanoparticles. TEM/high‐resolution TEM images showed that Ag and Ni were loaded on different locations on C3 N4, which indicated that during the photoreduction reaction Ag + obtained electrons from C3 N4 in the reduction reaction, whereas oxidation reactions proceeded on Ni nanoparticles. Photocatalytic hydrogen production experiments showed that C3 N4 ‐based hybrid heterojunctions can greatly improve the photocatalytic activity of materials. The possible reason is that two heterojunctions could form a long‐range electric field similar to the p‐i‐n structure in semiconductors. Most of the photogenerated carriers were generated and then separated in this electric field, thereby increasing the separation rate of electrons and holes. This further improved the photocatalytic activity of C3 N4 . Abstract : Creating heterojunctions : A long‐range electric field can be formed in C3 N4 loaded with two metal nanoparticles, Ni and Ag. Ohmic contact and Schottky contact are constructed on one single C3 N4 nanoparticle in between Ag and C3 N4 and Ni and C3 N4 . Photocatalytic hydrogen production experiments show that C3 N4 ‐based hybrid heterojunctions can greatly improve the photocatalytic activity of materials.